The Ethics of AI Usage from Perspective of the Qur'an - Fauzi, Rifqi Muhammad; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Amid the hustle and bustle of modern times, technology advances rapidly, unveiling a new face illuminated with dazzling lights. One of the technologies widely utilized in recent times is artificial intelligence, commonly known as AI. The Qur'an, as a guide for humanity, offers solutions to social problems. It remains timeless and consistently relevant to contemporary issues as they arise. One such contemporary challenge is the ethical use of technology. This study employs a qualitative approach. Through qualitative research, the researcher can gain a comprehensive and in-depth understanding of a specific issue. For data collection, the study utilizes library research methods, drawing on books, journals, and other media relevant to the topic. The conclusion of this research emphasizes that the use of Artificial Intelligence (AI) requires a strong ethical foundation to ensure it provides optimal benefits without harming humanity or causing damage. From the perspective of the Qur'an, the ethical principles include several key points: Justice in Usage – Ensuring AI is not misused or monopolized arbitrarily. Responsibility – Being accountable for activities involving AI to prevent unintended negative consequences. Avoiding Harm – Using AI appropriately while considering potential future impacts of misuse. Providing Benefit – Employing AI as a tool to ease human tasks and promote mutual assistance. The application of AI will be far more effective and beneficial if it adheres to the principles outlined in the Qur'an.